Cardiac Rehabilitation Therapy Trends in South Korea: an Epidemiologic Analysis Using Korean National Health Insurance System Database - Jin-seong Kim; Se-haeng Jo; Su-jin Lee; Tae-seung Song; Jin-woo Jung; Jeehyun Yoo (Physical Therapy Korea)
Background: Interest in cardiac rehabilitation therapy has been increasing in Korea after the addition of cardiac rehabilitation as a benefit item in the National Health Insurance Service in 2017. However, few epidemiological studies have characterized cardiac rehabilitation in Korea. Objects: To assess the national epidemiological data on cardiac rehabilitation therapy in Korea from 2017 to 2023. Methods: This study analyzed MM453, a prescription code for cardiac rehabilitation therapy in the Health Insurance Review and Assessment database. The data reviewed included the total number of cases per year and the number of cardiac rehabilitation therapy prescriptions per 100,000 people, along with sex and age distribution of patients undergoing cardiac rehabilitation therapy. Results: The number of cardiac rehabilitation therapy prescriptions in Korea increased from 4,443 in 2017 to 15,646 in 2023 (252.1% increase in 7 years). The incidence per 100,000 person-years rose from 8.64 in 2017 to 30.22 in 2023. The number of males undergoing therapy increased from 3,183 (incidence: 12.35) in 2017 to 11,276 (incidence: 43.53) in 2023. The number of females undergoing therapy increased from 1,260 (incidence: 4.91) in 2017 to 4,370 (incidence: 16.89) in 2023. The highest number of patients undergoing therapy from 2017 to 2023 was observed in the 60s age group (patients: 4,747, incidence: 9.17), followed by the 70s, 50s, and > 80s age groups. Conclusion: From 2017 to 2023, the number of patients undergoing cardiac rehabilitation therapy in Korea increased consistently. The therapy is approximately 2.6 times more common in males than that in females and is predominantly administered to individuals in their 60s, followed by those in their 70s, 50s, and 80s and above.